Early supplementation with zinc proteinate does not change rectal microbiota but increases growth performance by improving antioxidant capacity and plasma zinc concentration in preweaned dairy calves - Liu, Junhao; Yu, Xin; Ma, Fengtao; Wo, Yeqianli; Jin, Yuhang; Hashem, Nesrein M.; Sun, Peng (Frontiers in Veterinary Science, 2023)
The present study evaluated the effects of early supplementation with zinc proteinate (ZnP) or zinc oxide (ZnO) for 2 weeks on the growth performance, redox status, plasma trace element concentrations, and rectal microbiota of preweaned dairy calves. 60 newborn healthy female Holstein dairy calves, with initial body weight (BW): 41.33 ± 0.62 kg, were randomly allocated to 5 groups of 12 each: a control group (CON); three groups supplemented with 261 (L-ZnP), 523 (M-ZnP), and 784 (H-ZnP) mg/day ZnP, equivalent to 40, 80, and 120 mg/day zinc, respectively; and one group supplemented with 232 mg/day ZnO, equivalent to 180 mg/day zinc (ZnO). Zinc supplements were administered on days 1–14, and the calves were followed up until day 70. Zinc supplementation increased total dry matter intake (DMI) and starter DMI compared with the CON group (p < 0.01). The final BW, average daily gain, and feed efficiency were higher in the M-ZnP, H-ZnP, and ZnO groups (p < 0.05). The incidence of diarrhea on days 1–28 was reduced by zinc administration (p < 0.01), whereas the incidence on days 29–56 was lower in the M-ZnP and ZnO groups (p < 0.05). Serum glutathione peroxidase activity, total antioxidant capacity, immunoglobulin G and plasma zinc concentrations were increased linearly (p < 0.05), while the serum concentration of malondialdehyde was decreased linearly (p < 0.01), as the dose of ZnP increased. ZnP yielding 80 mg/day zinc had similar effects as ZnO yielding 180 mg/day zinc, except that final BW was higher in the ZnO group (p < 0.05). At the phylum level, ZnO decreased the relative abundance of Firmicutes while increasing the abundance of Bacteroidetes (p < 0.05). At the genus level, ZnO increased the relative abundances of Prevotella, Subdoligranulum, and Odoribacter (p < 0.05). These findings indicated that early supplementation with ZnP did not affect the rectal microbiota of preweaned dairy calves but increased their growth performance, antioxidant capacity, and plasma zinc concentration. In summary, ZnP is an organic zinc source with greater bioavailability than ZnO for preweaned dairy calves. Early dietary supplementation with ZnP yielding 80 mg/day zinc is recommended.